Resolving ABO discrepancies by serological workup-an analysis of few cases - P., Arumugam; Hamsavardhini, Swathandran; J., Ravishankar (International Journal of Research in Medical Sciences, 2017)
Background: ABO discrepancies occur whenever the results of red cell grouping and serum grouping are in disagreement. The reasons for discrepancies both clinical and technical have to be sorted out. Further analysis is essential to resolve such discrepancies. If discrepancies are encountered, the interpretation of the ABO grouping has to be delayed until the same has been resolved. The aim of the study was to resolve ABO discrepancies encountered, by serological work up. Methods: All cases of discrepant samples received between August 2014 and May 2016 at the Department of Transfusion Medicine, The Tamilnadu Dr. MGR Medical University, Chennai, India were analyzed to determine the etiology by serological workup. Results: A total of twenty-one samples were analyzed and resolved. Fifteen cases of Type IV discrepancy, two cases of Type II discrepancy, one case Type III discrepancy, one case Type I discrepancy and two cases of technical errors were identified. Conclusions: ABO discrepancies can be resolved serologically if properly worked up. As ABO blood grouping is indispensible in blood transfusion service, it is imperative to resolve such discrepancies before transfusion.